2015
DOI: 10.1007/s10880-015-9418-7
|View full text |Cite
|
Sign up to set email alerts
|

Parenting an Infant with a Congenital Anomaly: How are Perceived Burden and Perceived Personal Benefits Related to Parenting Stress?

Abstract: This study aimed to characterize parents' negative (perceived burden) and positive (perceived personal benefits) perceptions about parenting an infant with a congenital anomaly (CA), and to investigate their role in parenting stress. Forty-three couples (43 mothers and 36 fathers) whose 6-month-old infants had a CA completed several questionnaires: the Impact on Family Scale-Revised, the Positive Contributions Scale, and the Parenting Stress Index-Short Form. The results showed similarities between maternal an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
6
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 46 publications
4
6
0
Order By: Relevance
“…For example, they discussed family support both emotionally and financially, acceptance of their children “like a normal child,” using spirituality to make meaning of their child’s condition, and the importance of having a valued social circle of friends and neighbors. Our findings are also consistent with Fonseca et al (2015), who reported that how parents perceive their child’s condition can be an important factor to increase parental adaptation and positive parenting practices.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…For example, they discussed family support both emotionally and financially, acceptance of their children “like a normal child,” using spirituality to make meaning of their child’s condition, and the importance of having a valued social circle of friends and neighbors. Our findings are also consistent with Fonseca et al (2015), who reported that how parents perceive their child’s condition can be an important factor to increase parental adaptation and positive parenting practices.…”
Section: Discussionsupporting
confidence: 92%
“…In this sample, parents reported reliance on religion as a source of strength and meaning-making, consistent with other studies in the extant craniofacial literature (eg, Egan et al, 2011;Fonseca et al, 2015;Stock, Feragen, & Rumsey, 2016). Viewing their child's diagnosis with Apert syndrome as a test of their faith, a gateway to heaven or as part of God's plan particularly helped them with their own adaptation and coping with other people's reactions, staying grounded, taking care of their children, and promoting their children's independence and social skills.…”
Section: Discussionsupporting
confidence: 87%
“…We identified a wide range of parent‐reported impact, and while the median score was low, 5 (16%) parents returned a score of 35 or more, suggesting that their burden of care was significant. We saw that the median IOFS score for our cohort was similar to the mean scores reported in studies of children with congenital conditions including cerebral palsy and children with a range of congenital anomalies of the heart, nervous system, digestive system and urinary system 19‐21 . However, the impact on families caring for boys with PUV and moderate or severe CKD was significantly higher and was in a similar range to that reported by parents of children with brain cancer and chronic respiratory failure 22,23 .…”
Section: Discussionsupporting
confidence: 80%
“…We saw that the median IOFS score for our cohort was similar to the mean scores reported in studies of children with congenital conditions including cerebral palsy and children with a range of congenital anomalies of the heart, nervous system, digestive system and urinary system. [19][20][21] However, the impact on families caring for boys with PUV and moderate or severe CKD was significantly higher and was in a similar range to that reported by parents of children with brain cancer and chronic respiratory failure. 22,23 Our study findings that 62.5% of this subgroup felt like they lived on a roller coaster is similar to the level of that reported by families caring for childhood brain cancer.…”
Section: Discussionsupporting
confidence: 54%
“…Parental cognitions, such as perception of an event as predictable and controllable, may also minimize the impact of stress on adaptation by empowering the family unit to cope with demands [ 57 ]. High perceived stress has been shown to negatively influence family adaptation to chronic childhood disease [ 17 , 18 , 20 , 24 , 55 , 58 ] and contribute to increased negative perceptions of stressful situations, perceived manageability, and meaningfulness of life [ 28 ]. In our study, caregivers who reported their recent stress as more manageable also reported higher FQoL.…”
Section: Discussionmentioning
confidence: 99%